PENGARUH KEPEMIMPINAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CAPELLA ISUZU PEKANBARU - Lia Andira; Machasin Machasin; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of the work environment and leadership onemployee performance at the PT. Capella Isuzu Pekanbaru. The population in this studyincludes all employees at the PT. Capella Isuzu Pekanbaru, totaling 54 people. Primarydata were collected using a questionnaire as an instrument to prove the results of thestudy, to test the hypothesis in this study using linear regression analysis with the help ofthe SPSS program. The sampling technique that has been chosen is the census method (54employees at the PT. Capella Isuzu Pekanbaru). The results showed that: 1) there was apositive and significant effect of the on employee performance at the PT. Capella IsuzuPekanbaru, 2) there was a positive and significant influence work discipline on employeeperformance at the PT. Capella Isuzu Pekanbaru, 3) there is a positive and significantinfluence on the leadership and work discipline on employee performance at the PT.Capella Isuzu Pekanbaru. Keywords: leadership, work disciplin, employee performance